Recent developments in the assessment of the immune response to malaria, especially as related to vaccination: Variations in the virulence of Plasmodium gallinaceum for avian embryos after repeated passages in mosquitos and chickens - McGhee, R. Barclay (1979)
Inoculation of 1 × 10(6) parasites of Plasmodium gallinaceum from chicks infected with sporozoites into 10-day chicken embryos produced infections with wide ranges of peak parasitaemia. It is thought that these variations reflect alterations in the genetic moiety of the parasites after recombinations occurring during the sexual cycle in different batches of mosquitos.